Limacus flavus slug: Bioactive Molecules in the - Hayashida, Patricia Yumi (2021)
Snails and slugs were used as a treatment for many health problems, as skin and respiratory conditions and wound healing, since ancient times. Since the antimicrobial resistance became a major global thread, antimicrobial peptides have been considered as a potential source for development of new drugs, especially for drug-resistant bacteria. Nowadays reports confirm that the mucous secretions have antimicrobial, antiviral and antifungal properties. From the mucus of Limacus flavus slug, were isolated nineteen fractions with antimicrobial activity, but only two were chosen for identification and characterization. The mucus was obtained by thermal shock, lyophilized and submitted to acid extraction with acetic acid. The supernatant was pre-fractionated in Sep-Pak and shortly thereafter to Reverse-Phase High-Performance Liquid Chromatography. The fractions manually obtained were used to perform antimicrobial and assays, lastly submitted to mass spectrometry (MS/MS). The characterization was performed by bioinformatics analysis with the tool Peaks®X+ and compared with the NCBI and Uniprot-Swissprot database; also the physicochemical parameters of the samples were evaluated with online programs. The fractions are antimicrobial peptides for presenting sensibility to inhibit Micrococcus luteus A270, both samples are hydrophilic molecules and has under 20 residues in its composition. By the comparison of the data from SDS-PAGE gel and Peaks, both have Mw <3KDa, LFMP-003 (AVAALKFEAGN) and LFMP-005 (NFAAGCLGVTTADDNALE). When treated with DMSO, were isolated eleven fractions, but only three were selected for identification. The mucus showed greater inhibition for filamentous fungus (Aspergillus niger), yeast fungus (Cryptococcus neoformans), Gram-positive bacteria (Bacillus subtilis, Micrococcus luteus) and Gram-negative bacteria (Enterobacter cloacae). The fractions did not show hemolytic activity for human blood cells (erythrocytes). Fractions sequences were analyzed by tandem mass spectrometry (LC-MS / MS) and identified with PeaksX+ software, showing Mw <3kDa, LFMP-FP005 (WLGH), LFMP-FP006 (DLQW), LFMP-FP009 (YLRW), respectively. By bioinformatic analysis, LFMP-FP005 is CAMP, LFMP-FP006 is AAMP and LFMP-FP009 is a neutral AMP. All of the five peptides isolated from Limacus flavuss mucus exhibited a wide-spectrum of antimicrobial activity against Gram-positive and Gram-negative bacteria, yeast fungi and filamentous fungi.